2013
DOI: 10.4048/jbc.2013.16.2.214
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Risk Factors in a Defined Population: Weighted Logistic Regression Approach for Rare Events

Abstract: PurposeThis study aimed to determine out risk factors for female breast cancer in a low socioeconomic population in Iran.MethodsBetween 2007 and 2009, a total of 25,592 women who were ensured by the Imam Khomeini Relief Foundation participated in this screening program. The characteristics of patients diagnosed with breast cancer (n=111) were compared with those of control cases (n=25,481). In this study, we used relogit analysis (rare event logistic regression) with a weighting method using program Zelig.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 20 publications
3
32
0
Order By: Relevance
“…Some studies (Naieni et al, 2007) have come to the same conclusions as the present study, while some others have reported a significant association (Ghiasvand et al, 2011). Consistent with other epidemiological researches (Naieni et al, 2007;Ghiasvand et al, 2011;Ghiasvand et al, 2012;Zare et al, 2013), the results of the current study in consistent with other studies (Ren, 2012;Ronco et al, 2012b;Toleutay et al, 2013) indicated a significant relationship between family history of breast cancer and increased risk of breast cancer. This finding suggests the existence of genetic and environmental factors that are common among families.…”
Section: Discussionsupporting
confidence: 83%
“…Some studies (Naieni et al, 2007) have come to the same conclusions as the present study, while some others have reported a significant association (Ghiasvand et al, 2011). Consistent with other epidemiological researches (Naieni et al, 2007;Ghiasvand et al, 2011;Ghiasvand et al, 2012;Zare et al, 2013), the results of the current study in consistent with other studies (Ren, 2012;Ronco et al, 2012b;Toleutay et al, 2013) indicated a significant relationship between family history of breast cancer and increased risk of breast cancer. This finding suggests the existence of genetic and environmental factors that are common among families.…”
Section: Discussionsupporting
confidence: 83%
“…Some have shown that using the pills only trivially increased breast cancer risk and this was limited to those who used the pills for a long time 18,19. The other studies that have reported inconsistent results are not negligible 14,2022. Bethea et al20 examined the relationship between using contraceptive pills and emergence of breast cancer and found that using contraceptive pills and the term of using the pills were significantly related to development of breast cancer in African American women.…”
Section: Introductionmentioning
confidence: 99%
“…Marchbanks et al14 studied women ranged from 35 to 64 years old and found no significant relationship between breast cancer risk and using contraceptive pills. Veisy et al21 found a significant relationship between the term of using contraceptive pills and breast cancer, while Zare et al22 found a that using the pills significantly decreased risk of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the results of the present study were heterogeneous and the difference among studies or Tau 2 = 0.18. From 7 analyzed studies, 3 studies showed no significant relation between obesity and breast cancer (8,17,18). Out of 7 analyzed studies, 5 studies reported no significant relation between overweightness and breast cancer in women (8,17,18,21,23).…”
Section: Effect Of Exposurementioning
confidence: 99%
“…In one article (8), overweightness was the protecting factor and 4 studies showed no significant relation between overweightness and breast cancer (17,18,21,23).…”
Section: Effect Of Exposurementioning
confidence: 99%